A TiO2 nanotube network electron transport layer for high efficiency perovskite solar cells. Issue 7 (3rd February 2017) - Gao, Xianfeng; Li, Jianyang; Gollon, Sam; Qiu, Ming; Guan, Dongsheng; Guo, Xiaoru; Chen, Junhong; Yuan, Chris
Abstract : A TiO2 nanotube network ETL is developed for perovskite solar cells, presenting significantly improved performance over a conventional TiO2 mesoporous scaffold layer. Abstract : The electron transport layer (ETL) plays a critical role in high efficiency perovskite solar cells. In this study, an anodic TiO2 nanotube film was transformed into a TiO2 nanotube network film, which maintained its advantage as an efficient ETL for perovskite solar cells. Compared with the mesoporous TiO2 nanoparticle ETL, the TiO2 nanotube network ETL can increase the efficiency of perovskite solar cells by 26.6%, which is attributed to its superior charge collection property and light trapping ability. The results confirm the importance of optimizing the electron collecting layer and suggest another way to design and fabricate novel perovskite solid state solar cells, potentially by using a TiO2 nanotube network film as an alternative high efficiency electrode.